When Positive Ischemic Response on Treadmill Test Implies Otherwise: One Overlooked Pitfall on TMT - Rifanda, Dmitri Muhammad; Parama, M. A. L.; Putra, Teuku Muhammad Haykal; Widodo, Wishnu Aditya (The Indonesian Heart Association, 2022)
Background:Particular ischemic process that portrayed in Electrocardiogram (ECG) changes bear similar depiction to different conditions, one of them is hypokalemia. On the other hand, Treadmill Test (TMT) has been used for decades for risk stratifying and diagnosing coronary artery disease as a non-invasive, safe and affordable screening test. However, using ECG changes as interpretation, TMT could have incidence of false positive results reported in various conditions, one of which is hypokalemia. The aim is to report a case of positive ischemic response resemblance in TMT of patient with severe hypokalemia. Case Illustration:A-43-years-old female with history of unstable angina pectoris with risk factors of diabetes mellitus and hypertension underwent several examinations. Computed Tomography Coronary Angiography (CTCA) showed a 60% stenosis lesion in Left Anterior Descending (LAD) coronary artery. Within 3 minutes of TMT the ECG showed ST-segment depression in lead II, III, aVF, V1-V6 and prominent elevation in lead aVR. Fear of left main coronary artery occlusion, the test was terminated and the patient was immediately planned for urgent Percutaneous Coronary Intervention (PCI). The result indicated non-significant coronary lesion. Potassium concentration of 1.87 mmol per liter and troponin levels were normal. Unbeknownst before, the patient had multiple episodes of vomiting for a whole day and felt dehydrated prior to the TMT. Patient then treated for potassium implementation and discharged uneventfully. Conclusion:Hypokalemia could induce widespread ST-Segment depression or ST-Segment elevation in right limb lead. Peculiarly in context of stress testing or accompanied with chest pain, it is difficult to differentiate ECG changes in hypokalemia with true myocardial ischemia. Hypokalemia should be considered when TMT result is not concordance with true myocardial ischemia. This article has a related Erratum.